STRATEGI PEMBINA DALAM MEMBENTUK AKHLAK PESERTA DIDIK DI SMA BOARDING SEKOLAH ISLAM ATHIRAH BUKIT BARUGA MAKASSAR - Sukira; Mustamin; Raehana, Syarifa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines mentor strategies in shaping students’ moral character at SMA Boarding School of Sekolah Islam Athirah Bukit Baruga Makassar. The objectives of this research are to: (1) analyze the moral characteristics of students in the boarding school environment; (2) identify the strategies employed by mentors in fostering students’ morality; and (3) explore the supporting and inhibiting factors influencing the implementation of these strategies. This study adopts a qualitative research approach, which allows for an in-depth exploration and interpretation of data related to the research focus. Data were analyzed to reveal patterns of thought and practices applied by mentors in shaping students’ moral behavior within the boarding school context. The findings indicate that: (1) students’ moral character in the boarding environment is dynamic and diverse, influenced by differences in regional background, culture, and family upbringing; (2) mentors implement five primary strategies in fostering students’ morality, namely role modeling (uswah hasanah), habituation, motivation, disciplinary consequences, and prayer; and (3) supporting factors include the consistent implementation of rules and strong collaboration among dormitory staff, school authorities, and parents, while inhibiting factors include low self-awareness, lack of motivation for self-improvement, and students’ unstable psychological conditions during identity formation.